Fishery-independent camera surveys provide novel observations of white sharks (Carcharodon carcharias) off coastal Alabama - Drymon, J. Marcus; Jargowsky, Amanda E.; Switzer, Theodore S.; Hightower, Crystal L.; Powers, Sean P. (Frontiers in Marine Science, 2025)
Determining the distributions of marine animals is a challenge, particularly for highly migratory species like sharks. In the United States, several shark populations are beginning to recover following exploitation, including the white shark (Carcharodon carcharias). Recently, reports of white sharks have increased in the northern Gulf of Mexico (hereafter Gulf), but determining whether these reports represent actual changes in distribution is difficult. Therefore, we examined two long-term fishery-independent camera datasets to assess whether the recent increase in reports of white sharks reflects changes in distribution or typical (albeit rare) events. Long-term fishery-independent stereo-baited remote underwater video (sBRUV) and remotely operated vehicle (ROV) datasets were examined. From 2010 – 2024, 8368 sBRUV and 2199 ROV surveys were conducted. From 2010 – 2023, no white sharks were seen on either camera gear, but two white sharks were observed on ROV videos in 2024. The first was a female estimated at 239 cm total length and the second was a male estimated at 191 cm total length. These observations lend support to the notion that recent reports of white sharks in the northern Gulf may indicate early evidence of range-edge expansion rather than increases in telemetry efforts or citizen observations. Studies like this one highlight the value of long-term, randomized, fishery-independent camera surveys for documenting changes in distribution for rare species.